The Role of Green-Digital Integration in Enhancing Competitive Advantage and Sustainability of Private Higher Education Institutions - Emiliana Sri Pudjiarti; Amsar Amsar; Parshuram Sahoo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study explores the role of green-digital integration in enhancing the competitive advantage and sustainability of private higher education institutions in Central Java, Indonesia. Through a sequential explanatory mixed-methods approach with quantitative dominance, the study involved 332 heads of study programs as the primary respondents and structural equation modeling (SEM) to examine the complexity of the relationship between green-digital integration, market-oriented innovation, digital leadership competency, and competitive advantage & sustainability. The results revealed that green-digital integration significantly influences the competitive advantage of higher education institutions. Theoretically, this study expands the understanding of the strategic integration of sustainable practices and digital transformation in the context of higher education. The study provides a new conceptual framework to understand how higher education institutions can achieve a competitive advantage through an integrated approach. Its practical implications include guiding higher education leaders in developing green digital strategies and demonstrating the importance of market-oriented innovation and digital leadership competency in transforming educational institutions. This study offers comprehensive insights into how private higher education institutions can integrate sustainability and digital imperatives to achieve sustainable competitive advantage in the era of global transformation. The research findings emphasize the need for a holistic approach to managing higher education, focusing on academic aspects and considering environmental, technological, and market dimensions.